Risk factors for feeding difficulties in children with cerebral palsy - Nur, Fadhilah Tia; Handryastuti, Setyo; Pusponegoro, Hardiono D. (Indonesian Pediatric Society, 2025)
Background Cerebral palsy (CP) is caused by brain injury sustained during development. It is a motor and posture disorder. Feeding problems are more likely to appear in children with severe motor impairment, leading to insufficient caloric intake and malnourished. Objective To indentify association between the Gross Motor Function Classification System (GMFCS) and CP type as risk factors of feeding difficulties in children with CP. Methods This cross-sectional study was conducted between January and September 2015, in a Pediatric Neurology Outpatient Clinic at a tertiary hospital in Surakarta, Indonesia. Nutritional status, feeding difficulties, and the GMFCS were used to assess children with CP. We performed Gross Motor Function Measure-88 to identify the GMFCS. Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2020 concerning child anthropometric standards was carried out to evaluate and classify nutritional status. Krick CP growth curve was used to compare spastic quadriplegia. Calorie intake was evaluated by dietary analysis and defined as adequate if it reached 13.9 kcal/cm body height (BH) ± 10%. Results The majority of CP patients (96.3%) were spastic, with quadriplegic and diplegic cases being the most common. Malnourished impacted 78% of all participants; in addition, 78% of participants reported having feeding difficulties, with roughly one-third having a high GMFCS score. The GMFCS scale on oromotor dysfunction (OMD) and bad postural control (BPC) showed statistically significant, with P values of 0.042 and 0.041, respectively. The GMFCS scale and spastic CP type is also statistically significant with BPC (OR 6.35;95%CI 3.29 to 24.12 and OR 4.32;95%CI 2.53 to 22.35, respectively). Sixty-eight% of children with CP were wasted, with 10% experiencing severely wasted. Conclusion Children with CP who have a higher GMFCS score and spastic CP are more likely to have feeding issues.